Road Geometric Horizontal Alignment Planning Using Manual Design Method (Case Study: Alternative Road Between Cibalong District â€“ Santolo Beach STA 0+000 to STA 2+500 Garut Regency, West Java) - Alif Ridho Alghiffari; Amanatullah Savitri (LEADER: Civil Engineering and Architecture Journal, 2023)
An alternative road between Cibalong District - Santolo Beach was made can provide solutions to traffic problems and provide security, comfort, and smooth traffic, and is expected to support economic development with easy access to Santolo Beach. This journal aims to design the geometric design of Alternative Roads in Cibalong District â€“ Santolo Beach STA 0+000 to STA 2+500 Garut Regency, West Java based on â€œ2021 Road Geometric Design Guidelinesâ€. This road planning uses data that is divided into primary data and secondary data. From the calculation,s it can be concluded that on a 2,500 km road, 4 different types of turns can be applied. Type Full Circle 1 (FC) uses a radius of 800 m, an arc length is 287,665 m, Type Full Circle 2 (FC) uses a radius of 800 m, arc length is 337,866 m, Type Spiral-Circle-Spiral 1 (SCS) uses a radius of 250 m, length arc 67,803 m, and the Spiral-Circle-Spiral 2 (SCS) type uses a radius of 250 m, arc length of 67,803 m. Road geometric planning that takes into account cost efficiency and safety is very important in the infrastructure development of an area, especially access to tourist areas that can support the local economy.